Strategi Promosi Penjualan Produk Melalui Content Marketing di Grand Hotel Preanger Bandung - Rizky Nurainun Denisya; Irena Novarlia; Gilang Pratama Putra (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The development of digital technology at this time plays a very important role for a product sales promotion, there are many things that need to be considered in a content marketing in a company, one of which is in the hospitality industry. Grand Hotel Preanger is a 5-star hotel located in the center of Bandung which has heritage characteristics and strongly maintains its authenticity. The purpose of this study is to determine how promotional strategies in increasing product sales through content marketing at Grand Hotel Preanger. In this study the authors used a qualitative descriptive research method with a case study approach and used SWOT analysis, namely calculating and deepening the EFAS and IFAS matrices. Data collection in this study used observation, interview, and documentation techniques. From the research results, it is found that the position of the product sales promotion strategy through content marketing at Grand Hotel Preanger is in quadrant I position, which means that it is very profitable for a company by utilizing strengths as opportunities for increasing the number of products produced, namely maintaining the brand image to customers and the characteristics of a heritage hotel by utilizing its beauty and strategic opportunities in the middle of downtown Bandung.